Integrated production of tambaqui and leafy vegetables in urban houses (Research, Society and Development, 2022)
Aquaponics emerges as an alternative for food production, which is managed by the principle of sustainable production, with a view of respect for the environment and comply with the current demands of a more conscious and demanding consumer market. This production refers to the integration between fish farming and the cultivation of hydroponic vegetables and/or leafy vegetables. The present study aimed to clearly and objectively demonstrate to the population the possibility of producing fish and vegetables in small spaces, especially in urban centers. The model fish species was tambaqui (Colossoma macropomum) and the model leafy vegetables were lettuce (Lactuca sativa), arugula (Eruca vesicaria ssp. Sativa), chicory (Cichorium intybus sub sp. Intybus) and watercress (Nasturtium officinale). The collected data showed good results regarding the growth of fish and leafy vegetables, providing information on the development and cultivation in low-cost urban aquaponic systems. We believe that these results will be of great value to the general population and that they will increase interest in this modality of healthy and low-coast food production.